2022
DOI: 10.1242/dmm.049109
|View full text |Cite
|
Sign up to set email alerts
|

Clinically relevant orthotopic xenograft models of patient-derived glioblastoma in zebrafish

Abstract: An accurate prediction of the intracranial infiltration tendency and drug response of individual Glioblastoma (GBM) cells is essential for personalized prognosis and treatment for this disease. However, the clinical utility of mouse PDOX models remains limited given current technical constraints including difficulty in generating sufficient sample numbers from small tissue samples and a long latency period for results. To overcome these issues, we establish zebrafish GBM xenografts of diverse origin, which can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The xenografted cells showed significant gene enrichment in categories, such as tumor metastasis, cell migration and epithelial-to-mesenchymal transition. This transcription identity suggests that the zPDX models can recapitulate the supportive tumor microenvironment that patient-derived cells need [95].…”
Section: Zebrafish Are Clinically Relevant Cancer Avatars Modelsmentioning
confidence: 92%
See 2 more Smart Citations
“…The xenografted cells showed significant gene enrichment in categories, such as tumor metastasis, cell migration and epithelial-to-mesenchymal transition. This transcription identity suggests that the zPDX models can recapitulate the supportive tumor microenvironment that patient-derived cells need [95].…”
Section: Zebrafish Are Clinically Relevant Cancer Avatars Modelsmentioning
confidence: 92%
“…Following the success of xenograft of human cancer cell lines, patient-derived xenografts models in zebrafish have been developed and used to assess different attributes of tumor behavior. zPDX models have since been established in multiple cancer types, including gastric cancer [92], colorectal cancer [73], breast cancer [83], non-small cell lung adenocarcinoma [93], pancreatic ductal adenocarcinoma [94] and others [68,74,95]. Ai et al highlighted the importance of an in vivo system to patient-derived cells by comparing the transcriptomic profile of glioblastoma multiforme (GBM) cells that were xenografted to zebrafish larvae brain to GBM cells grown in vitro in typical cell culture conditions.…”
Section: Zebrafish Are Clinically Relevant Cancer Avatars Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2010) demonstrated that NF1 knockdown increased ERK signaling and increased OPC proliferation in the developing spinal cord ( 109 ). Orthotopic xenografts and immunodeficient zebrafish models have also been developed for brain tumors ( 110 113 ). Although many of the zebrafish xenograft models used glioblastoma cells, Yuan et al.…”
Section: Zebrafish As Models For Plggmentioning
confidence: 99%
“…Primary GBM (glioblastoma) cells were cultured using three cell culture methods: organoid culture, neurosphere culture, and adherent culture, and then injected into the ZF. A comparison of these three culture types showed that attached culture GBM cells yielded the highest success rate, of 58% (attached cells) versus 25% (neurosphere) and 9% (organoid) [ 21 ].…”
Section: Disease Induction: How To Create a Fish Modelmentioning
confidence: 99%